Hydrogenolysis of Glycerol to Propylene Glycol: Energy, Tech-Economic, and Environmental Studies - Sun, Puhua; Zhang, Wenxiang; Yu, Xiao; Zhang, Jie; Xu, Ningkun; Zhang, Zhichao; Liu, Mengyuan; Zhang, Dongpei; Zhang, Guangyu; Liu, Ziyuan; Yang, Chaohe; Yan, Wenjuan; et al. (Frontiers in Chemistry, 2022)
Hydrogenolysis of glycerol to propylene glycol represents one of the most promising technologies for biomass conversion to chemicals. However, conventional hydrogenolysis processes are often carried out under harsh H2 pressures and temperatures, leading to intensive energy demands, fast catalyst deactivation, and potential safety risks during H2 handling. Catalytic transfer hydrogenolysis (CTH) displays high energy and atom efficiency. We have studied a series novel solid catalysts for CTH of glycerol. In this work, detailed studies have been conducted on energy optimization, tech-economic analysis, and environmental impact for both processes. The key finding is that relatively less energy demands and capital investment are required for CTH process. CO2 emission per production of propylene glycol is much lower in the case of transfer hydrogenolysis. The outcome of this study could provide useful information for process design and implementation of novel hydrogenolysis technologies for other energy and environmental applications.